Oxaliplatin in pre-treated patients: maybe not the match point? - Caparello, Chiara; Vasile, Enrico; Garajova, Ingrid; Ali, Asif; Giovannetti, Elisa (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Pancreatic cancer is an aggressive disease and is projected to become one of the major causes of cancer-related death in western countries. Intensification of first-line treatment with the use of polychemotherapeutic regimens (FOLFIRINOX, gemcitabine plus nab-paclitaxel) has significantly improved the overall survival and progression-free survival; as a consequence, the number of patients alive and fit for second-line treatment is increasing. However, the selection of the best second-line treatment is difficult and large phase III trials are urgently needed. After the positive results of oxaliplatin and fluorouracil combination in the CONKO-003 trial, two recent phase III studies, PANCREOX and NAPOLI-1, investigating the use of second-line chemotherapy after gemcitabine-based first-line, showed controversial results. Giving the practice-changing advances rapidly growing in last years and the multiple therapeutic strategies that are becoming available for the treatment of pancreatic cancer, the real issue seems to be the optimal sequence of treatment much more than second-line treatment.